1982
DOI: 10.1063/1.331316
|View full text |Cite
|
Sign up to set email alerts
|

Failure prediction for long length optical fiber based on proof testing

Abstract: A new method for reliability assurance of long length optical glass fibers is presented. This method is based on a simple equation by fracture-mechanics theory and provides failure probability prediction for fibers after proof testing. The prediction is made by using dynamic fatigue data obtained by simple tensile tests and failure number during proof testing. The experimental results are found to be in good agreement with those predicted by the theory, and it is verified that the method is useful to make reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…Our calculation was based on Mitsunaga's equation [3]. As a result of reducing the bend strain by downsizing the glass, we confirmed that the reliability of the downsized fiber was sufficient characteristic for practical use when bent a small diameter (FIT=0.01, bend R=5mm, ten turns (used for five years)).…”
Section: Fig 2 Fiber Structure Of High-a Downsized Mmfmentioning
confidence: 73%
“…Our calculation was based on Mitsunaga's equation [3]. As a result of reducing the bend strain by downsizing the glass, we confirmed that the reliability of the downsized fiber was sufficient characteristic for practical use when bent a small diameter (FIT=0.01, bend R=5mm, ten turns (used for five years)).…”
Section: Fig 2 Fiber Structure Of High-a Downsized Mmfmentioning
confidence: 73%
“…So, the fibers have a high probability of breaking. We calculated the fiber breaking probability with a Weibull distribution and we used (4) as the calculation formula [9,10].…”
Section: A Analysis Of Leaked Light Distribution and Intensitymentioning
confidence: 99%
“…The failure probability F of the optical fiber is calculated with ( 3 ) [7] F = l The fiber bends when there is water in the splice enclosure, so the n = 20 value should be used in the calculation. We use this sensor at every splice enclosure in optical fiber networks.…”
Section: E Reliabilitymentioning
confidence: 99%